2015
DOI: 10.1097/iae.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Functional and Morphologic Characteristics of Lamellar Macular Holes With and Without Lamellar Hole-Associated Epiretinal Proliferation

Abstract: Eyes with LMH and LHEP were associated with poorer visual acuity, larger LMH diameters, thinner retinal thickness, and higher incidence of ellipsoid disruption compared with eyes without LHEP, suggesting a process involving more severe retinal tissue loss and injury. Both LMH with and without LHEP seemed to be stable configurations over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
117
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 16 publications
8
117
2
2
Order By: Relevance
“…They suggested that LHEP is a distinct clinical entity and LMH with LHEP has a poorer visual acuity, larger hole diameter, thinner retina, and higher incidence of ellipsoid disruption than LMH without LHEP. 6 These findings were supported by other investigations. 7 The baseline visual acuity, as well as improvement of visual acuity after surgery, has been reported as worse in LMH with LHEP, 8 although the results are controversial.…”
supporting
confidence: 82%
“…They suggested that LHEP is a distinct clinical entity and LMH with LHEP has a poorer visual acuity, larger hole diameter, thinner retina, and higher incidence of ellipsoid disruption than LMH without LHEP. 6 These findings were supported by other investigations. 7 The baseline visual acuity, as well as improvement of visual acuity after surgery, has been reported as worse in LMH with LHEP, 8 although the results are controversial.…”
supporting
confidence: 82%
“…In line with previous observations, standard ERMs were more common than LHEP, with only 11 of 84 eyes showing no trace of standard ERM. 1,6,7 It must be noted that identifying the presence of trace amounts of LHEP in cases with a prominent, standard ERM and vice versa may be difficult and easily should be avoided because in several cases, 1 type of epiretinal material is predominant but not exclusive. 7,9 The presence of LHEP does influence some morphologic and functional features of LMHs.…”
Section: In This Retrospective Study We Show That In Eyesmentioning
confidence: 99%
“…[1][2][3][4] The associated epiretinal material can be thin and highly reflective (the so-called standard epiretinal membrane [ERM]) or of medium reflectivity with focal variations in thickness (the so-called lamellar hole-associated epiretinal proliferation [LHEP]). [5][6][7][8][9] Histopathologic analysis has shown that myofibroblasts dominate in highly reflective membranes, whereas membranes of medium reflectivity consist primarily of fibroblasts and hyalocytes. 10,11 As a consequence, it has been hypothesized that membranes of medium reflectivity should possess weaker contractive properties than standard ERMs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, LMH are defined by qualitative aspects found on OCT, according to the International Vitreomacular Traction Study (IVTS), such as (1) irregularity of the foveal contour, (2) internal break in the fovea, (3) dehiscence of the internal fovea from the external retina, or (4) lack of a full-thickness defect with preservation of the photoreceptor layer [2, 3]. LMH management is still a matter of debate, but in asymptomatic LMH patients, observation complemented with serial OCT follow-up is usually the preferred approach, while in patients complaining of metamorphopsia or visual acuity changes, a surgical approach is to be considered in order to restore both foveal anatomy and visual performance [4, 5]. However, studies have demonstrated varying anatomical and visual outcomes after surgery [6-9] that may in part be explained by lamellar hole-associated epiretinal proliferations (LHEP) [10], which are related with a minimal traction component compared to typical hyperreflective epiretinal membranes (ERM).…”
Section: Introductionmentioning
confidence: 99%